Aplicações com spline cúbico - CORRÊA, Silvio Luiz da Silva (2024)
The application of numerical cubic spline interpolation methods is shown in a didactic manner. The figure of the map of Salinópolis/PA is obtained using the free or natural spline and the figure of population growth in Salinópolis/PA from 2016 to 2022 through the restricted spline comparing with the Maltusian model with population growth rate constant signal.